NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN CERPEN SURGA JUGA DI TELAPAK KAKI AYAH KARYA SAFIRA ATALLA - Nurhalisa Nurhalisa; Nuraini Kasman; Rustam Efendy Rasyid; Suhartini Khalik (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the value of character education. This research uses a descriptive method with a qualitative approach. The focus of this research is the character education value of discipline and national spirit. The words or sentences found in the story are the data for this research. While the source of the data is a collection of short stories, ‘Heaven is Also on the Soles of Daddy's Feet’ by Safira Atalla, The data collection techniques used are library techniques, note-taking techniques, and data analysis based on Miles & Huberman data analysis techniques. The results showed that there are six values of discipline character education, namely: Father, your time is precious for me; Father, a simple doctor who is generous; he survives as a father for his child; women in the eyes of Father; the glory of a father's heart; the role of Father is often overlooked; and three values of national spirit character education, namely life is joy and sorrow; father is a yentara; and an athlete with his father.